Light-emitting metalenses and meta-axicons for focusing and beaming of spontaneous emission - Yahya Mohtashami (Nature Portfolio, 2021)
Controlling radiation emission using metamaterials is of interest for light sources and other applications. Here, the authors develop generalized phased-array metasurface equations and design metasurface axicons and lenses to collimate and focus the spontaneous emission, respectively.